Giant placental chorioangioma discovered at 29 weeks’ gestation: a case report - Cherrabi, Fatimazahra; Moukit, Mounir; Kouach, Jaouad; Rahali, Driss Moussaoui; Dehayni, Mohammed (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Chorioangiomas are the commonest non-trophoblastic tumors of placenta with an estimated incidence of 1%. The majority of them are small, asymptomatic and only found by careful pathologic examination of the placenta. Occasionally, they can attain a large diameter (≥ 4-5cm) resulting in what is termed ‘giant chorioangioma’ with a high feto-maternal morbidity and mortality rates. We report a case of giant chorioangioma discovered accidentally during a routine obstetric ultrasound. Expectant management was adopted. Ultrasound follow-up revealed several fetal complications; an elective caesarean section was made giving birth to a premature new-born with enormous hepatosplenomegaly, died on the first day of life. Diagnosis and management of chorioangioma represents a stringent challenge for obstetricians due to its potentially serious antenatal complications.